(untitled) (Terr@ Plural, 2021)
The northeastern region of the state of Paraná, Brazil, is still little known in its paleontological and stratigraphic aspects. This work focused on Devonian outcrops located in Arapoti and Piraí do Sul and aimed at the recognition of sedimentary facies and the definition of taphofacies, with the intention of paleoenvironmental interpretation and stratigraphic correlation. Three different facies were identified, representing shoreface to offshore environments, and also three taphofacies were defined: T1 characterizes the most proximal and destructive environments, T2 represents lower shoreface environments and T3, originated offshore. The base of the section is correlated to the early Devonian, Ponta Grossa Formation, Siluro-Devonian Sequence (Neopraguian-Eoemsian) due to the visible contact with sandstones of the Furnas Formation, and the top, due to the presence of microfossils, is positioned in the São Domingos Formation, Devonian Sequence I (Neoemsian-Eoeifelian).